Safety and efficacy of aflibercept in combination with fluorouracil, leucovorin and irinotecan in the treatment of Asian patients with metastatic colorectal cancer. Issue 3 (14th April 2016) - Chong, Dawn Q; Manalo, Mary; Imperial, Marlowe; Teo, Patrick; Yong, Grace; Ng, Matthew; Tan, Iain BH; Choo, Su Pin; Chua, Clarinda
Abstract: Aim: To evaluate the safety and efficacy of the combination therapy of fluorouracil, leucovorin and irinotecan (FOLFIRI) and aflibercept in Asian patients with metastatic colorectal cancer (mCRC), who had progressed after oxaliplatin‐based chemotherapy. Methods: This is a retrospective analysis of 19 mCRC patients who received FOLFIRI and aflibercept (4 mg/kg intravenously) every 2 weeks via a Named Patient Program (supported by Sanofi Aventis) in Singapore. Treatment was administered until disease progression or unacceptable toxicities. Kaplan–Meier method was used to estimate progression‐free survival (PFS) and overall survival (OS). Efficacy and toxicities were summarized using descriptive statistics. Statistical analysis was performed using STATA 12.0 software. Results: The majority (84%) of the patients were of chinese ethnicity. The median age was 59 years, with 63.2% of the patients having an Eastern Cooperative Oncology Group status of 1. Four patients (21.1%) achieved partial response and 8 patients (42.1%) achieved stable disease. After a median follow‐up of 9.6 months [95% confidence interval (CI), 2.2–13.1 months], the median OS was 11.6 months (95% CI, 6.1 to not‐estimable), and median PFS was 4.1 months (95% CI, 2.2–5.9). Majority of the toxicities were grade 1–2, and include leucopenia (84.2%), anemia (73.7%), liver enzyme elevation (68.4%) and fatigue (68.4%). The most frequently reported grade 3 toxicities were neutropenia and neutropenic complications (both 15.8%). All adverse events resolved with supportive management. Conclusion: The clinical benefit and safety profile of the combination of FOLFIRI/aflibercept in Asian patients with mCRC are consistent with that of Western population. FOLFIRI/aflibercept may be an appropriate therapeutic option in Asian patients with mCRC previously treated with an oxaliplatin‐based regimen.